171k views
4 votes
$2(x+6) + $40 = $4x
Please explain

1 Answer

5 votes


2(x+6)+40=4x\\2x+12+40=4x\\2x+12+40-4x=0\\2x-4x+52=0\\-2x+52=0\\-2x=-52\\x=26

Basically multiply the 2 inside the bracket, then addition and subtraction. For the -2x=-52 part. Move -2 to divide the -52, you'll get x = -52/-2 as you'll get x = 26 because minus * minus or minus divide minus will always be positive.

User Panupan
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.